Consumer Protection in Application-Based Gold Trading Transactions: A Sharia Economic Law Perspective - F. Fauzan (Golden Ratio of Data in Summary, 2026)
Technological developments and innovation have significantly transformed the economic and commercial landscape. This digital convenience has extended even to tertiary needs, especially the buying and selling of gold. However, behind this convenience, a major debate has emerged within Islamic law regarding cashless gold transactions, particularly those conducted through the Pegadaian Digital application. Therefore, it is essential to thoroughly examine the Islamic legal perspective on online, cashless gold trading while also considering aspects of business ethics, social responsibility, and consumer protection to ensure that these practices comply with Islamic law. This study aims to analyze consumer protection in digital application–based gold trading transactions from the viewpoint of Islamic economic law. As technology continues to progress, online gold transactions have become an increasingly popular alternative investment. Nonetheless, several critical issues arise regarding contract transparency, the physical existence of gold, and the clarity of rights and obligations between sellers and buyers. This research uses a qualitative approach with a case study focusing on a single online gold trading platform in Indonesia. Data were gathered through interviews, document analysis, and a review of Islamic legal literature. The findings suggest that despite the platform offering features that facilitate transactions, there are still shortcomings in consumer protection, especially concerning the principles of legal certainty (al-tsubūt), justice (‘adl), and information transparency (ṣidq).